2008
DOI: 10.1016/s0213-9111(08)75347-0
|View full text |Cite
|
Sign up to set email alerts
|

Prácticas sexuales de chicos y chicas españoles de 14-24 años de edad

Abstract: The results of this study indicate that sexual behavior differs between genders, with females having a lower number of sexual partners and more frequently using a condom in vaginal intercourse but less frequently in oral sex and anal intercourse. In view of these data, we believe that gender should be taken into account when designing and implementing preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 17 publications
3
4
0
2
Order By: Relevance
“…In relation to the sociodemographic characteristics of the sample analyzed, it is noted that the mean age of individuals diagnosed with an STI was lower than in the case of those who did not have them. This result coincides with the publications in the scientific literature, considering the young population as one of the groups most exposed to STIs [ 22 , 23 , 24 ] along with other vulnerable groups such as gay men [ 5 , 25 , 26 , 27 , 28 ], men who have sex with men (MSM), transgender people, injecting drug users, women, sex workers, and immigrants, especially irregular immigrants [ 18 , 29 , 30 , 31 , 32 , 33 ]. Likewise, in a recent study on HIV and other STI epidemiology, it is observed that in 2006 the higher number of cases of some STIs such as syphilis, gonorrhea, chlamydia trachomatis, and lymphogranuloma venereum occurred in young adults between 25–44 years old [ 34 ], the age range in which the mean age of persons positively diagnosed with STIs is found in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In relation to the sociodemographic characteristics of the sample analyzed, it is noted that the mean age of individuals diagnosed with an STI was lower than in the case of those who did not have them. This result coincides with the publications in the scientific literature, considering the young population as one of the groups most exposed to STIs [ 22 , 23 , 24 ] along with other vulnerable groups such as gay men [ 5 , 25 , 26 , 27 , 28 ], men who have sex with men (MSM), transgender people, injecting drug users, women, sex workers, and immigrants, especially irregular immigrants [ 18 , 29 , 30 , 31 , 32 , 33 ]. Likewise, in a recent study on HIV and other STI epidemiology, it is observed that in 2006 the higher number of cases of some STIs such as syphilis, gonorrhea, chlamydia trachomatis, and lymphogranuloma venereum occurred in young adults between 25–44 years old [ 34 ], the age range in which the mean age of persons positively diagnosed with STIs is found in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the percentage of women in PR who reported this behavior (13.2%) was lower than that of U.S. women (31%), although similar to data from Mexican Americans [13]. Also, consistent with studies in the United States and in other Hispanic populations is the observation that men have more sexual partners than women [13,23,24], and that younger women have a higher prevalence of multiple sexual partners than older women [13]. This pattern is consistent with a study of adolescents in PR where the prevalence of sexual relations with intercourse was similar in both sexes, which contrasts with what has been traditionally reported and still prevails in many other countries (higher prevalence of early age at sexual initiation among men than women).…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the level of knowledge of HIV and other STIs was medium to low; important gaps were observed regarding forms of transmission and general prevention. Other studies, focused on Colombian adolescents [17, 29] and Spaniard adolescents [26, 34], have reported similar results. This situation highlights the need to modify erroneous sexual beliefs and to provide reliable information to adolescents.…”
Section: Discussionsupporting
confidence: 69%